A Cross-Sectional Survey Study to Assess the Smart Phone Usage and Academic Performance in Medical Professional Students at National Institute of Ayurveda, Jaipur - Yadav, Chhaju Ram; Chudasama, Hardik; Yadav, Sarika (Asian Journal of Biological and Life Sciences, 2025)
Introduction: A two-year cross-sectional survey of 550 medical professional students assessed smartphone usage patterns and perceived academic impact. Results: Majority female (53.64%); WhatsApp most used (45.63%); Kriya Sharir identified as most interesting subject by 14% respondents. Conclusion: Responsible smartphone use benefits academic learning; self-regulation recommended.
Keywords: Smartphone use; Academic performance; Medical students